Calidad de los servicios básicos en el Recinto San Agustin, Cantón Babahoyo, Los Ríos - Marcial Dominguez, Johnson Wilber (2020)
The case study was carried out in the San Agustin Campus located in the Dr. Camilo Ponce parish of the Babahoyo Canton of the Los Ríos Province - Ecuador, determining that the quality of the basic services available to the population of said sector does not They are of quality, since in recent years the population has presented diseases associated with the quality of the water supplied and the management of waste. 44% of the study population indicated that the water and sewerage services are of poor quality, where 64% indicate that the water they receive is piped, the collection of waste is poor in 61%. They also indicate that 36% of the population do not have drinking water directly from the public network since they obtain it by other means not mentioned, in the same way, 31% of the population stated that they have a public sewerage network in front of their properties, so they have another individual system of excreta disposal. The study was carried out under the qualitative-quantitative, inductive deductive methodology, with the collection of data that accepted the participation with the survey carried out and analyzing the situation of the objects under study. With the results of the study, it is proposed to improve the quality control of the basic services provided to the population, establishing a maintenance and expansion plan for the drinking water and sewerage system and specifying strategies that improve the collection of waste and that in turn once they succeed in satisfying users.